Comparative analysis of high-risk HPV and TCT results in 193 postmenopausal women (Journal of research in medical and health sciences, 2025)
Objective, To explore the infection status of high-risk human papillomavirus (HR-HPV) in postmenopausal women and the value of liquid-based thin-layer cytology test (TCT) in cervical lesion screening. Methods: A retrospective analysis was conducted on the HR-HPV and TCT results of 193 postmenopausal women aged 55 and above who underwent colposcopy at Luancheng People's Hospital in Shijiazhuang from 2018 to 2023. Biopsy results were used as the gold standard to calculate and compare the screening efficacy of the two methods. Results: Among the 193 women, 162 were TCT positive, with a positive rate of 83.94%; 107 were HR-HPV positive, with a positive rate of 55.44%. The HR-HPV positive rate was significantly lower than that of TCT （χ² = 109.003, P < 0.001）. Among the 108 biopsy-positive patients, TCT detected 97 cases, with a sensitivity of 89.81%; HR-HPV detected 78 cases, with a sensitivity of 72.22%. In the TCT-negative group, 11 cases of pathological positivity were detected, with a missed diagnosis rate of 10.19%; in the HR-HPV-negative group, 30 cases of pathological positivity were detected, with a missed diagnosis rate of 27.78%. Conclusion: In cervical cancer screening for postmenopausal women, TCT has a high sensitivity and low missed diagnosis rate, while HR-HPV has a relatively low sensitivity and high missed diagnosis rate. The combined screening strategy of HR-HPV and TCT can improve the detection rate of cervical lesions and is an ideal cervical screening model for postmenopausal women.
Keywords: High-risk HPV; TCT; Postmenopausal women; Cervical lesion; Screening efficacy